Vacant yet invasible niches in forest community assembly. (30th June 2020) - Gauzere, Pierre; Morin, Xavier; Violle, Cyrille; Caspeta, Ivanna; Ray, Courtenay; Blonder, Benjamin
Abstract: It is controversial whether communities are saturated with species, or have vacant niches. The prevalence of vacant niches and the processes likely to promote their existence are poorly known. We used a process‐based forest gap‐model to simulate plant community dynamics in 11 sites along a climatic gradient across central Europe. We then used hypervolume analyses to study the existence of vacant niches (seen as empty volumes in the trait space of local species pools and communities), and we tested for the effect of abiotic (environmental filtering) and biotic (competition) processes on the functional hypervolumes along the climatic gradient. Last, we performed invasion simulations to assess the invasibility of detected vacant niches. Our results suggest that empty volumes in trait space are common, can arise from both abiotic and biotic processes and are more likely in cold climates. We also showed that most vacant niches are invasible. Synthesis . Our work supports the view that niche space is unsaturated, and that many viable ecological strategies are absent from these forest communities. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article .